The Prevalence, Pattern, Knowledge, Attitude, and Behavior regarding Tobacco Use among border Students of Public Sector Medical University: A cross-sectional study - Abdul Basit, Ali; Akbar, Hamza; Lehrasab, Saeed (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Smoking is one of the most common problems among students globally. It severely impacts smokers' health and leads to addiction. This study investigates the prevalence, attitude, and beliefs about smoking among students living in dormitories at Rawalpindi Medical University. Materials and Method: A self-administered questionnaire, based on the Global Association of Tobacco Survey covering sections of prevalence, knowledge, attitude, and behavior along with the pattern of tobacco smoking was distributed to 249 students living in hostels of Rawalpindi Medical University. Results: In general, the predominance of smoking among students living in quarters was 38.1% with more among males at 45.3% as compared to females at 7.7%. Most students have correct knowledge of the smoking hazards, but still, there should be awareness sessions to motivate students to quit this bad habit. A positive attitude toward quitting smoking was observed. 41.3 % of participants also use other drugs besides tobacco. This thing is alarming and appropriate steps should be taken to eradicate this. Conclusion and recommendations: The percentage of smokers among students living in Dormitories of Rawalpindi Medical University was significantly high. Students know the negative aspects of smoking and they have a positive attitude towards quitting. It may be useful to train students about techniques or methods so that they can combat stresses of various types. Counseling sessions should be arranged for medical students, to reduce smoking practices among students living in dormitories.